Do Board Size, Female Directors and Ownership Dispersion Influence Financial Performance of Cooperatives? An Analysis Using Upper Echelons Theory - Muhammad, Kamaruzzaman; Ghani, Erlane K.; Ilias, Azleen; Ibrahim, Mohd Adha; Jamil, Nurul Nazlia; Anwar, Nazratul Aina Mohamad; Razali, Fazlida Mohd (International Journal of Economics and Financial Issues, 2024)
This study employs the upper echelons theory to examine the factors that influence the financial performance of cooperatives in Malaysia. Specifically, three factors are selected in this study, namely board size, female directors, and ownership dispersion, in relation to the financial performance of the cooperatives in Malaysia. In this study, a content analysis was performed on 145 cooperatives’ annual reports. This study shows that the number of board members has no effect on the financial performance of the cooperatives, indicating that a small board with knowledgeable members can also outperform a larger board with less expertise. This study also shows that female directors do no impact on the financial performance of cooperatives. Finally, this study demonstrates that the disbursement of members in the cooperatives has no effect on their financial performance. The findings in this study provide a relevant perspective on the financial performance of cooperatives that can help regulators understand and provide proper guidance to the cooperatives. This study also provides empirical evidence on the relationship between board size, female directors, ownership dispersion, and the financial performance of the co-operatives, adding to the financial reporting literature.